SNPs no gene da HSC70 e suas implicações na carcinicultura e conservação dos estoques de camarão-da-amazônia (Macrobrachium amazonicum) - Blanck, Danielly Veloso (2013)
Macrobrachium amazonicum is an endemic species in South America, which has been exploited by artisanal fisheries in northern and northeastern Brazil. The overexploitation of this species has led to the decline of its natural stocks. This scenario affects the riverine communities and the genetic status of populations of this crustacean. In this context, the aquaculture emerges as a sustainable alternative to soften this impact over the natural stocks. A molecular view of adaptations and modifications in response to environmental variables is important for understanding the biology, distribution and capacity of this crustacean to adapt to different conditions and geographic regions, either in its natural habitat or in captivity. Considering these aspects, SNPs markers within fitness-related candidate gene emerge as promising tools for selection and detection of genetic structure in natural populations and to verify their correlation with complex traits of interest in farming. In this study, the aim was to investigate SNPs in the HSC70 (70-kilodalton Heat Shock Cognate) gene under two approaches: (1) the prospection and association of SNPs to growth traits in a captive population of M. amazonicum (CAUNESP); and (2) the SNPs prospection, characterization of the variability and genetic structure of two wild stocks of M. amazonicum (Tocantins and Paracauari rivers, both in Para state). To the firsty study, were carried out an experimental performance of these prawns, undergone to two stocking densities (normal and intensification conditions). Growth traits (total and abdominal length, and total abdominal and hepathopancreas weight) and sex were determined during the harvesting. The SNPs effects on these phenotypic variables were tested in a mixed model conducted by the Proc Mixed of the SAS program. Twelve SNPs were identified. Among them, only two SNPs (C256T and T907C) and two haplotypes (H7 and H10) presented effects of interest. These effects comprised several traits, including density and population class interactions. The most important effects were found in the normal density of the farming and on females. SNPs effects were not detected in high stocking density treatment. xix So, this fact excludes the possibility of using this information to the farming intensification of M. amazonicum. However, these results consist of relevant information for the development of high performing culture lines of M. amazonicum by Marker Assisted Selection. The SNPs effects on females may indicate the involvement of the HSC70 gene in the reproductive development of the species. In the second study, 13 SNPs were characterized in the Tocantins river population and six SNPs in the Paracauari river population. No significant deviation from Hardy Weinberg equilibrium was found. However, linkage disequilibrium was detected among some pairs of SNP loci. Both stocks showed high haplotype diversity. The haplotype diversity was 0.712 and 0.596 for the Tocantins and Paracauari river populations, respectively. These values were significantly different between the populations (P ≤ 0.05). AMOVA indicated that almost all variability occurs within the populations and these stocks are not genetically differentiated (FST = -0,00048). Apparently, if based on the diversity and the absence of genetic structure information, the anthropic action has not caused drastic effects on the genetic status of these two populations of M. amazonicum. These results prove that SNP markers within HSC70 gene are useful in establishing strategies for managing breeding programs as well as programs for the conservation of the species focus of this study.